Nursing care in view of the family functionality of patients with Amyotrophic Lateral Sclerosis (Research, Society and Development, 2022)
This study aims to describe the scientific evidence regarding nursing care in relation to the family functionality of a patient with amyotrophic lateral sclerosis. Methodology: This is an integrative literature review, carried out between February and March 2021, using publications indexed in the electronic database: Latin American and Caribbean Literature on Health Sciences (LILACS), Scientific Electronic Library Online (SciELO) and Nursing Database (BDENF), In total, 9 articles were found that met the inclusion criteria of this work. The results showed that the level of dependence of the patient with ALS is a contributing factor to cause physical and mental stress on the caregiver, with the overload being spontaneously proportional to the degree of dependence of the patient. Thus, it can be concluded that caregivers of patients with ALS are overloaded in relation to care and need support and guidance to cope with the demands related to the daily life of patients with ALS. And one of the alternatives is the constitution of help groups composed of nursing professionals and caregivers that work as a place for exchanging knowledge and emotional help.